2021
DOI: 10.21203/rs.3.rs-620847/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Novel Pyroptosis-related Gene Signature for Prognostic Prediction of Head and Neck Squamous Cell Carcinoma

Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) is an extremely heterogeneous malignant cancer with poor prognosis. Pyroptosis is defined as a novel inflammation-dependent programmed cell death. However,the pyroptosis-associated genes expression in HNSCC and their relationship with prognosis is still indistinct.Material and Methods: We acquired HNSCC patients’ mRNA expression information from TCGA and GEO publicly available. We compared tumor issues and adjacent normal tissues in terms of the gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…16 Latest two studies had reported the prognostic prediction of pyroptosis signature in HNSCC. 36,37 They identified both few PRGs with a 4- To accurately evaluate the pyroptosis features in each HNSCC patient, we constructed a pyroptosis score system using the PCA algorithm. We found that patients with low pyroptosis scores usually presented shorter survival times and higher death rates, suggesting that low pyroptosis scores might predict poor outcomes in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Latest two studies had reported the prognostic prediction of pyroptosis signature in HNSCC. 36,37 They identified both few PRGs with a 4- To accurately evaluate the pyroptosis features in each HNSCC patient, we constructed a pyroptosis score system using the PCA algorithm. We found that patients with low pyroptosis scores usually presented shorter survival times and higher death rates, suggesting that low pyroptosis scores might predict poor outcomes in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicated that pyroptosis plays a crucial role in regulating antitumor immunity and inflammation 16 . Latest two studies had reported the prognostic prediction of pyroptosis signature in HNSCC 36,37 . They identified both few PRGs with a 4‐gene and a 5‐gene signature, respectively, and analyzed the immune cell infiltration of the risk model simply.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [14] constructed eight-PRG signature (AIM2, BAK1, GZMA, GZMB, IRF1, NOD2, TNF, and TP63) to predict the survival in bladder cancer (BC) patients. Qian et al [15] performed a novel PRG signature (GSDME, IL1B, NLRP1, and NLRP6) for prognostic prediction of head and neck squamous cell carcinoma. In EC, Chen et al [23] recently analyzed 33 PRGs between tumour samples and normal samples and obtained six pyroptosisrelated prognostic DEGs (GPX4, GSDMD, GSDME, IL6, NOD2, and PYCARD).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the expression of pyroptotic inflammasome GSDMD is decreased in gastric cancer (GC) cells, which promotes the proliferation of GC cells [10]. Recent studies have shown that PRG signatures can be used as effective prognostic markers in ovarian cancer [12], lung cancer [13], bladder cancer [14], and squamous cell cancer in the head and neck [15]. However, the prognostic value of PRGs in EC has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 52 PRGs were extracted from prior publications [14][15][16][17], previous pyroptosis-related studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31] and MSigDB database (v7.4), [32], respectively (Supplementary Table S1). The expression data in all the three datasets were normalized to fragment per kilobase million (FPKM) values before comparison.…”
Section: Identification Of Differentially Expressed Pyroptosis Relate...mentioning
confidence: 99%